(untitled) (Biocenosis, 2026)
Sandy beaches are dynamic ecosystems that host a high level of biodiversity. Species such as the ghost crab (Ocypode quadrata) and the fiddler crab (Uca thayeri) inhabit these environments and play key roles in the stability and functioning of coastal ecosystems. This study analyzed the diversity, abundance, and distribution of these species at Puerto Vargas Beach, Limón, Costa Rica so as to assess their relationship with coastal erosion. A total of 144 transects were conducted, comparing sites with and without erosive processes. Environmental variables such as temperature, salinity, pH, slope, and beach width were measured. The results indicate that the abundance of these crustaceans is significantly higher in eroded sectors (p = 0.03), where factors such as slope (p = 0.003), temperature (p = 0.01), and the reduction in beach width (p = 0.02) act as modulators of their spatial distribution. It is concluded that, although erosion alters coastal morphodynamics, these species exhibit niche specialization that allows them to exploit new microhabitats. The research highlights the vulnerability of these bioindicators to the loss of thermal refuges caused by the retreat of the coastal forest. It also emphasizes the urgency of integrating the monitoring of benthic fauna—referring to organisms that inhabit coastal bottoms and sediments— into management and climate adaptation strategies for protected areas in the South Caribbean.